2022
DOI: 10.1002/marc.202100917
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically Modified Cellulose Nanofibers‐Enveloped Solid Lipid Microparticles for Improved Antioxidant Cargo Retention

Abstract: This study introduces a cellulose nanofiber surfactant system, in which the surface is hydrophobically modified with different alkyl chain structures for the effective envelopment of solid lipid microparticles (SLMs). To endow bacterial cellulose nanofibers (BCNFs) with excellent ability to assemble at the lipid-water interface, alkyl chains with designated molecular structures, such as decane, didecane, and eicosane, are covalently grafted onto the BCNF surface. Interfacial tension and interfacial rheology me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The appropriate introduction of single alkyl chains into BCNFs increases their adhesion to the O/W interface, and the introduction of dialkyl chains leads to a more improved interfacial assembly with the aid of chain configuration. 45,46 BCNF diC18 is expected to have an excellent ability to assemble at the O/W interface, as two C18 alkyl chains per unit cellulose ring will readily adhere to oil drops while retaining its hydrophilicity, which is quite comparable to the case of using BCNF diC18 grafted with a single C18 alkyl chain per unit cellulose ring (Figure 2a). To prove this, the wettability of BCNF C18 and BCNF diC18 was examined by measuring the contact angle of a sessile drop of water on a flat glass slide coated with each dried BCNF film (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The appropriate introduction of single alkyl chains into BCNFs increases their adhesion to the O/W interface, and the introduction of dialkyl chains leads to a more improved interfacial assembly with the aid of chain configuration. 45,46 BCNF diC18 is expected to have an excellent ability to assemble at the O/W interface, as two C18 alkyl chains per unit cellulose ring will readily adhere to oil drops while retaining its hydrophilicity, which is quite comparable to the case of using BCNF diC18 grafted with a single C18 alkyl chain per unit cellulose ring (Figure 2a). To prove this, the wettability of BCNF C18 and BCNF diC18 was examined by measuring the contact angle of a sessile drop of water on a flat glass slide coated with each dried BCNF film (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6 Despite this, emulsions suffer from long-term stability and undesirable exposure to light and oxygen that may lead to deactivation of the encapsulated actives. 7 Alternatively, emulsiontemplated microcapsules and vesicles, which can effectively enclose the inner solvent phase containing the desired actives within a shell material have been proposed. 8,9,[30][31][32] While photopolymerizable perfluoropolyethers (PFPEs) and low molecular weight poly(ethylene glycol diacrylate) (PEGDA) have been exploited as the shell material for the microencapsulation of a broad range of solvents, they are either not biocompatible, only offer a limited selection of compatible solvents, or leave shell debris after rupture.…”
Section: Introductionmentioning
confidence: 99%
“…13,18,19 Recent studies have also shown that hydrophobically modified nanofibers, including ethyl hydroxyethyl cellulose and hydroxypropyl methyl cellulose acetate succinate, can induce the formation of cubic or lamellar phases in lipid-water dispersions while interacting strongly with the lipids without being admitted into the internal phases. 20,21 Such nanofibrillary materials with high aspect ratios are featured to form a tight and dense fibrillary membrane at the lipid-water interface owing to their amphiphilic nature. [21][22][23] These findings suggest that properly selecting lipids and surfactants with a well-adjusted composition is critical for stabilizing suspended lipid particles.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Such nanofibrillary materials with high aspect ratios are featured to form a tight and dense fibrillary membrane at the lipid-water interface owing to their amphiphilic nature. [21][22][23] These findings suggest that properly selecting lipids and surfactants with a well-adjusted composition is critical for stabilizing suspended lipid particles.…”
Section: Introductionmentioning
confidence: 99%